2016
DOI: 10.1093/scipol/scw019
|View full text |Cite
|
Sign up to set email alerts
|

Universities and external engagement activities: Particular profiles for particular universities?

Abstract: Studies of universities' external engagement have found that individual and discipline-level characteristics explain most of the participation in different kinds of external engagement activities, but characteristics at the institutional level are often not studied explicitly. In this paper, we analyze how five different forms of external engagement are influenced by a range of factors, using a multilevel regression approach on a complex combined dataset including a survey to 4400 Norwegian academics and detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 25 publications
2
30
1
1
Order By: Relevance
“…A final organizational factor relates to the overall features of the university and the way these might influence the external engagement of academics. Thune et al (2016) study the influence of university-level characteristics on the external engagement of academics, concluding that these characteristics, when controlled for the influence of individual and discipline-level factors, do not explain much about the differences in external engagement among academic staff. According to the authors, only consultancy and commercialization activities are influenced by university-level factors, while dissemination, external training and research collaboration are types of external engagement that are not influenced by institutional-level factors.…”
Section: Theoretical Redescription Of the Key Dimensions (Abduction)mentioning
confidence: 97%
“…A final organizational factor relates to the overall features of the university and the way these might influence the external engagement of academics. Thune et al (2016) study the influence of university-level characteristics on the external engagement of academics, concluding that these characteristics, when controlled for the influence of individual and discipline-level factors, do not explain much about the differences in external engagement among academic staff. According to the authors, only consultancy and commercialization activities are influenced by university-level factors, while dissemination, external training and research collaboration are types of external engagement that are not influenced by institutional-level factors.…”
Section: Theoretical Redescription Of the Key Dimensions (Abduction)mentioning
confidence: 97%
“…In order to investigate Italian academics' PE activities, we asked respondents seven questions largely inspired by previous research (Abreu et al 2011;Teichler et al 2013;Thune et al 2016). The first referred to people-based activities.…”
Section: Public Engagement Activities: Diffusion and Dimensionsmentioning
confidence: 99%
“…Data have also been collected at the individual level, however, mainly through surveys within different types of studies: within international studies on changes in the academic profession (Bentley and Kyvik 2011;Teichler et al 2013); and within national studies on the activities carried out by specific categories of researchers (Davies 2013;Royal Society 2006); on knowledge exchange between academics and the business, public and third sectors (Abreu et al 2011); on researchers' public engagement activities (Hamlyn et al 2015;Jensen 2011;Kreimer et al 2011;Scamuzzi et al 2015); and on university external engagement activities (Thune et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While changes in governance are generally expected to lead to changes in social behavior, there is no consensus in the literature regarding how governance reforms related to KE policies have changed academics' behavior patterns (de Rijcke et al, 2016;Gläser, 2019). In general, studies have shown that ASE is, to a large extent, driven by the motivations of individual academics and their networks of relationships with industry and other sectors of society (e.g., Perkmann et al, 2013;Thune et al, 2016).…”
Section: Introductionmentioning
confidence: 99%